No evidence for a causal link between Helicobacter pylori infection and Irritable bowel syndrome: a Mendelian randomization study - Wang, Chenchen; Zhang, Jing; Han, Fengli; Liu, Dong; Han, Yuying (Frontiers in Microbiology, 2024)
Background: Although clinical studies have revealed a potential link between Helicobacter pylori(H. pylori) infection and Irritable Bowel Syndrome (IBS), the causal relationship between them remains unknown. The objective of this study was to investigate whether H. pylori infection is causally associated with IBS.Method: A two-sample Mendelian Randomization (MR) analysis using the inverse variance weighted (IVW), Weighted mode, weighted median and MR-Egger methods was performed. We used the publicly available summary statistics data sets of genome-wide association studies (GWAS) for H. pylori infection in individuals of European descent (case = 1058, control = 3625) as the exposure and a GWAS for noncancer illness code self-reported: IBS (case = 10,939, control = 451,994) as the outcome.We selected 10 single nucleotide polymorphisms at genome-wide significance from GWASs on H. pylori infection as the instrumental variables. The IVW, Weighted mode, weighted median and MR-Egger methods all provided consistent evidence that suggests a lack of causal association between H. pylori and IBS. MR-Egger regression revealed that directional pleiotropy was unlikely to be biasing the result (intercept = -1e-04; P = 0.831). Cochran's Q test and the funnel plot indicated no evidence of heterogeneity and asymmetry, indicating no directional pleiotropy.The results of MR analysis support that H. pylori infection may not be causally associated with an increased risk of IBS.